Penanggalan Kekebalan Pejabat Diplomatik: Kebijakan Hukum Negara Pengirim atau Negara Penerima? - Sari, Annisa Asfida; Putra, Akbar Kurnia (Faculty of Law, Universitas Jambi, 2021)
Article 29 of the 1961 Vienna Convention stipulates that diplomatic officers are inviolable, may not be arrested or detained. They must be treated with respect and receiving countries must take appropriate steps to prevent attacks on their persons, freedoms and dignity. So the consequence arising from the inviolability of a diplomatic official is immunity from the jurisdiction of the receiving country. However, the jurisdictional immunity possessed by diplomatic officials can be waived by the sending country as contained in Article 32 of the 1961 Vienna Convention. This article aims to find out how the mechanism in the issuance of immunity (immunity waiver) by the sending country against diplomatic officials. The results of the study show that the subject who has the right to waive the immunity of diplomatic officials who commit violations in the receiving country is the sending country. This waiver of immunity can be carried out after an application is submitted by the receiving country and submitted by the Head of State, Minister of Foreign Affairs or the Head of the Diplomatic Representative of the sending country.